Effects of Nano Copper Additive on Thermal Conductivity of Magnetorheological Fluid at Different Environment Temperature - Mohd Salleh, Abdul Rahim; Izwan, Ismail; S. N., Aqida (Trans Tech Publications, 2017)
Low thermal conductivity of magnetorheological (MR) fluid limits its potential to be applied in high temperature environment. Recently, enhancing thermal conductivity of similar fluids through addition of nano copper has alracted to address the problem. This paper presents the effects of nano copper addition on thermal conductivity properties of MR fluid at diiYerctu environment temperatures. The nano copper added MR fluid samples wert: synthesized with carhunyl iron powder in hydruulic oil. Hie sample were then stabilised with addition of fumed silica and were homogenized using ultrasonic bath. Thermal conductivity of the samples and references material was measured using thermal property analyser The environment temperature of the samples was controlled by waterbath. intubation method. The results showed that enhancement of thermal conductivity with the presence of copper nano panicles was higher it 40 vol% of CIP compared to 20 vol% of CIP and a slight variation in thermal conductivity of MR fluid was observed in environment temperatures of 30-70 C. . This finding leads to development of new class of magnetorlogical fluid with enhanced thermal properties